Religious Behavior And Self-Defense Method: A Study Of Patient With Bipolar Disorder - Wiwik Setiyani (Psikis : Jurnal Psikologi Islami, 2020)
Human life is dynamic in maintaining the balance of their soul. Life problems such as family conflict have an impact on mental balance. This study analyzed a bipolar patient, based on the result of observation, in-depth interviews, and relevant documents from one of the mental hospitals. Freud and Jung were chosen as a method for analyzing the concept of self-defense. The purpose of the study was to analyze bipolar psychiatric condition by finding the factors that influenced it. The findings revealed that life experience formed spirituality with zikir continually and practiced prayer despite the bipolar condition. Self-defense by continuing to maintain religious behavior as religious healing is one of the alternative solutions by involving the role of the family.